LINGKUNGAN SEKOLAH DAN PROSES BELAJAR MENGAJAR DI SDK SANTA MARIA KOTA MADIUN - Fransiska Amelia; Ola Rongan Wilhelmus (Bahasa Indonesia, 2022)
The school environment as a formal educational institution, is organized, systematic, multilevel and follows clear and strict requirements. The school environment is a component or an integral part of the school. The Catholic school environment should have a characteristic that is based on Christ in his ministry, always prioritizing love and evangelical freedom. A good Catholic school environment is expected to encourage an effective and efficient learning process. The purpose of this study (1) to understand a good and healthy school environment, (2) good and healthy teaching and learning process. (3) analyze the extent to which the school environment has an influence on the implementation of the teaching and learning process at at Santa Maria Catholic Elementary School. Respondents in this study amounted to 6 teachers at at Santa Maria Catholic Elementary School, namely two principals and four teachers. The analytical method used is inductive. From the results of this study, respondents understand that the school environment is a healthy and comfortable learning environment, a place for education and training, as well as a second home, where the teaching and learning process takes place, and a place for interaction between school residents.